Antimicrobial Susceptibility Profiling and Genomic Diversity of Multidrug-Resistant Acinetobacter baumannii Isolates from a Teaching Hospital in Malaysia - Kong, Boon Hong (National Institute of Infectious Diseases, 2011)
The resistance phenotypes and genomic diversity of 185 Acinetobacter baumannii isolates obtained from the intensive care unit (ICU) of a local teaching hospital in Kuala Lumpur from 2006 to 2009 were determined using antimicrobial susceptibility testing and pulsed-field gel electrophoresis (PFGE). Antibiogram analyses showed that the isolates were fully resistant to β-lactam antimicrobials and had high resistance rates to the other antimicrobial agents tested. However, the isolates were susceptible to polymyxin B. Resistance to cefoperazone/sulbactam was only detected in strains isolated from 2007 to 2009. Some environmental isolates and an isolate from the hands of a healthcare worker (HCW) had identical resistance profiles and PFGE profiles that were closely related to patient isolates. Cluster analyses based on the PFGE profiles showed there was a persistent clone of endemic isolates in the ICU environment. The transmission route from HCWs to fomites to patients, which caused a long-term infection in the ICU of the University Malaya Medical Centre, was observed in this study. These data provide a better understanding of A. baumannii epidemiology within the hospital and the possible transmission routes. Knowledge of changes in the resistance rates of A. baumannii in our local hospital will improve antimicrobial therapy.